Moral Emotions and Their Brain Structural Correlates Across Neurodegenerative Disorders. - Baez, Sandra; Trujillo-Llano, Catalina; de Souza, Leonardo Cruz; Lillo, Patricia; Forno, Gonzalo; Santamaría-García, Hernando; Okuma, Cecilia; Alegria, Patricio; Huepe, David; Ibáñez, Agustín; Decety, Jean; Slachevsky, Andrea (J Alzheimers Dis, 2023)
BACKGROUND: Although social cognition is compromised in patients with neurodegenerative disorders such as behavioral variant frontotemporal dementia (bvFTD) and Alzheimer's disease (AD), research on moral emotions and their neural correlates in these populations is scarce. No previous study has explored the utility of moral emotions, compared to and in combination with classical general cognitive state tools, to discriminate bvFTD from AD patients. OBJECTIVE: To examine self-conscious (guilt and embarrassment) and other-oriented (pity and indignation) moral emotions, their subjective experience, and their structural brain underpinnings in bvFTD (n = 31) and AD (n = 30) patients, compared to healthy controls (n = 37). We also explored the potential utility of moral emotions measures to discriminate bvFTD from AD. METHODS: We used a modified version of the Moral Sentiment Task measuring the participants' accuracy scores and their emotional subjective experiences. RESULTS: bvFTD patients exhibited greater impairments in self-conscious and other-oriented moral emotions as compared with AD patients and healthy controls. Moral emotions combined with general cognitive state tools emerged as useful measures to discriminate bvFTD from AD patients. In bvFTD patients, lower moral emotions scores were associated with lower gray matter volumes in caudate nucleus and inferior and middle temporal gyri. In AD, these scores were associated with lower gray matter volumes in superior and middle frontal gyri, middle temporal gyrus, inferior parietal lobule and supramarginal gyrus. CONCLUSION: These findings contribute to a better understanding of moral emotion deficits across neurodegenerative disorders, highlighting the potential benefits of integrating this domain into the clinical assessment.
Keywords: Alzheimer Disease; Brain; Emotions; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Morals; Neuropsychological Tests

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Neuroanatomical Comparison of the "Word" and "Picture" Versions of the Free and Cued Selective Reminding Test in Alzheimer's Disease. - Slachevsky, Andrea; Barraza, Paulo; Hornberger, Michael; Muñoz-Neira, Carlos; Flanagan, Emma; Henriquez, Fernando; Bravo, Eduardo; Farías, Mauricio; Delgado, Carolina (J Alzheimers Dis, 2018)
Episodic memory tests with cued recall, such as the Free and Cued Selective Reminding Test (FCSRT), allow for the delineation of hippocampal and prefrontal atrophy contributions to memory performance in Alzheimer's disease (AD). Both Word and Picture versions of the test exist but show different profiles, with the Picture version usually scoring higher across different cohorts. One possible explanation for this divergent performance between the different modality versions of the test might be that they rely on different sets of neural correlates. The current study explores this by contrasting the neural correlates of the Word and Picture versions of the FCSRT with voxel-based morphometry (VBM) in AD and healthy subjects. We predicted that the Picture version would be associated with different cortical regions than the Word version, which might be more hippocampal-centric. When comparing 35 AD patients and 34 controls, AD patients exhibited impairments on both versions of the FCSRT and both groups performed higher in the Picture version. A region of interest analysis based on prior work revealed significant correlations between free recall of either version with atrophy of the temporal pole and hippocampal regions. Thus, contrary to expectations, performance on both the Word and the Picture version of the FCSRT is associated with largely overlapping networks. Free recall is associated with hippocampal volume and might be properly considered as an indicator of hippocampal structural integrity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Cues; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation

Structural Anatomical Investigation of Long-Term Memory Deficit in Behavioral Frontotemporal Dementia. - Bertoux, Maxime; Flanagan, Emma C; Hobbs, Matthew; Ruiz-Tagle, Amparo; Delgado, Carolina; Miranda, Marcelo; Ibáñez, Agustín; Slachevsky, Andrea; Hornberger, Michael (J Alzheimers Dis, 2018)
Although a growing body of work has shown that behavioral variant frontotemporal dementia (bvFTD) could present with severe amnesia in approximately half of cases, memory assessment is currently the clinical standard to distinguish bvFTD from Alzheimer's disease (AD). Thus, the concept of "relatively preserved episodic memory" in bvFTD remains the basis of its clinical distinction from AD and a criterion for bvFTD's diagnosis. This view is supported by the idea that bvFTD is not characterized by genuine amnesia and hippocampal degeneration, by contrast to AD. In this multicenter study, we aimed to investigate the neural correlates of memory performance in bvFTD as assessed by the Free and Cued Selective Reminding Test (FCSRT). Imaging explorations followed a two-step procedure, first relying on a visual rating of atrophy of 35 bvFTD and 34 AD patients' MRI, contrasted with 29 controls; and then using voxel-based morphometry (VBM) in a subset of bvFTD patients. Results showed that 43% of bvFTD patients presented with a genuine amnesia. Data-driven analysis on visual rating data showed that, in bvFTD, memory recall & storage performances were significantly predicted by atrophy in rostral prefrontal and hippocampal/perihippocampal regions, similar to mild AD. VBM results in bvFTD (pFWE<0.05) showed similar prefrontal and hippocampal regions in addition to striatal and lateral temporal involvement. Our findings showed the involvement of prefrontal as well as medial/lateral temporal atrophy in memory deficits of bvFTD patients. This contradicts the common view that only frontal deficits explain memory impairment in this disease and plead for an updated view on memory dysfunctions in bvFTD.

Tau Platelets Correlate with Regional Brain Atrophy in Patients with Alzheimer's Disease. - Slachevsky, Andrea; Guzmán-Martínez, Leonardo; Delgado, Carolina; Reyes, Pablo; Farías, Gonzalo A; Muñoz-Neira, Carlos; Bravo, Eduardo; Farías, Mauricio; Flores, Patricia; Garrido, Cristian; Becker, James T; Lopez, Oscar L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Intracellular neurofibrillary tangles are part of the core pathology of Alzheimer's disease (AD), which are mainly composed of hyperphosphorylated tau protein. OBJECTIVES: The purpose of this study is to determine whether high molecular weight (HMW) or low molecular weight (LMW) tau protein levels, as well as the ratio HMW/LMW, present in platelets correlates with brain magnetic resonance imaging (MRI) structural changes in normal and cognitively impaired subjects. METHODS: We examined 53 AD patients and 37 cognitively normal subjects recruited from two Memory Clinics at the Universidad de Chile. Tau levels in platelets were determined by immunoreactivity and the MRI scans were analyzed using voxel-based morphometry in 41 AD patients. RESULTS: The HMW/LMW tau ratio was statistically different between controls and AD patients, and no associations were noted between HMW or LMW tau and MRI structures. In a multivariate analysis controlled for age and education level, the HMW/LMW tau ratio was associated with reduced volume in the left medial and right anterior cingulate gyri, right cerebellum, right thalamus (pulvinar), left frontal cortex, and right parahippocampal region. CONCLUSIONS: This exploratory study showed that HMW/LMW tau ratio is significantly higher in AD patients than control subjects, and that it is associated with specific brain regions atrophy. Determination of peripheral markers of AD pathology can help understanding the pathophysiology of neurodegeneration in AD.

First Symptoms and Neurocognitive Correlates of Behavioral Variant Frontotemporal Dementia. - Santamaría-García, Hernando; Reyes, Pablo; García, Adolfo; Baez, Sandra; Martinez, Angela; Santacruz, José Manuel; Slachevsky, Andrea; Sigman, Mariano; Matallana, Diana; Ibáñez, Agustín (J Alzheimers Dis, 2016)
BACKGROUND: Previous works highlight the neurocognitive differences between apathetic and disinhibited clinical presentations of the behavioral variant frontotemporal dementia (bvFTD). However, little is known regarding how the early presentation (i.e., first symptom) is associated to the neurocognitive correlates of the disease's clinical presentation at future stages of disease. OBJECTIVES: We analyzed the neurocognitive correlates of patients with bvFTD who debuted with apathy or disinhibition as first symptom of disease. METHODS: We evaluated the neuropsychological, clinical, and neuroanatomical (3T structural images) correlates in a group of healthy controls (n = 30) and two groups of bvFTD patients (presented with apathy [AbvFTD, n = 18] or disinhibition [DbvFTD, n = 16]). To differentiate groups according to first symptoms, we used multivariate analyses. RESULTS: The first symptom in patients described the evolution of the disease. AbvFTD and DbvFTD patients showed increased brain atrophy and increased levels of disinhibition and apathy, respectively. Whole brain analyzes in AbvFTD revealed atrophy in the frontal, insular, and temporal areas. DbvFTD, in turn, presented atrophy in the prefrontal regions, temporoparietal junction, insula, and temporoparietal region. Increased atrophy in DbvFTD patients (compared to AbvFTD) was observed in frontotemporal regions. Multivariate analyses confirmed that a set of brain areas including right orbitofrontal, right dorsolateral prefrontal, and left caudate were enough to distinguish the patients' subgroups.∥Conclusion: First symptom in bvFTD patients described the neurocognitive impairments after around three years of disease, playing an important role in the early detection, disease tracking, and neuroanatomical specification of bvFTD, as well as in future research on potential disease-modifying treatments.

So Close Yet So Far: Executive Contribution to Memory Processing in Behavioral Variant Frontotemporal Dementia. - Bertoux, Maxime; Ramanan, Siddharth; Slachevsky, Andrea; Wong, Stephanie; Henriquez, Fernando; Musa, Gada; Delgado, Carolina; Flanagan, Emma; Bottlaender, Michel; Sarazin, Marie; Hornberger, Michael; Dubois, Bruno (J Alzheimers Dis, 2016)
BACKGROUND: Memory impairment in behavioral variant frontotemporal dementia (bvFTD) is traditionally considered to be mild and attributed to prefrontal cortex dysfunction. Recent studies, however, indicated that some patients can present with a memory impairment of the hippocampal type, showing storage and consolidation deficits in addition to the more executive/prefrontal related encoding and strategic difficulties. OBJECTIVE: This study aimed to study the relationship between executive functions (EF) and memory processes in bvFTD via a data-driven approach. METHOD: Participants consisted of 71 bvFTD (among which 60.6% had a lumbar puncture showing non-Alzheimer biomarker profile) and 60 controls (among which 45% had amyloid imaging showing a normal profile). EF were assessed by the Frontal Assessment Battery, semantic/lexical verbal fluency tests, and forward/backward digit spans. Patients were split into amnestic (n = 33) and non-amnestic (n = 38) subgroups based on normative data (total recall score) from the Free and Cued Selective Reminding Test (FCSRT). Relationships between FCSRT subscores and EF measures were explored through hierarchical clustering analysis, partial correlation analysis with an EF component, and automated linear modeling. RESULTS: Convergent findings across the statistical approaches show that, overall, memory performance was independent from EF in bvFTD whereas the relationship was stronger in controls. Indeed, in bvFTD, memory performance did not cluster with EF, was not correlated with the EF component, and was only partially (4% - 12.7%) predicted by EF. DISCUSSION: These findings show that executive dysfunctions cannot solely explain the memory deficits occurring in bvFTD. Indeed, some patients present with a genuine amnesia affecting storage and consolidation abilities, which are independent from executive dysfunctions. On the clinical level, this study highlights the importance of revising the neuropsychological diagnosis criteria for bvFTD.